SISTEM MONITORING DAN PEMBERIAN PAKAN OTOMATIS PADA PETERNAKAN BURUNG DENGAN KONFIGURASI WI-FI DINAMIS ESP32 - Laksana, Danu Dwiki; Zaky, Umar (Jurnal Informatika Teknologi dan Sains (Jinteks), 2024)
The development of technology has greatly assisted humans in various activities, such as monitoring and feeding pets or livestock. Numerous studies have focused on implementing automated monitoring and feeding systems using Internet of Things (IoT) technology. This technology can be integrated with various other technologies, such as applications or websites. However, current Wi-Fi configurations are still hard coded into the program. This affects IoT devices, preventing them from connecting to different networks. Therefore, this research proposes the development of an application that can be used to monitor and feed animals by adding dynamic Wi-Fi configuration to the ESP32 microcontroller. Wi-Fi that can be configured dynamically makes IoT devices more flexible in choosing Wi-Fi networks.